Unusual Lymphocytic and Granulomatous Pattern in Inflammatory Bowel Disease: A Case Report and Review of the Literature - Zhang, MD, PhD, Yujie; Hussain, MD, Aleena; Arshad, MD*, Ayesha (North American Journal of Medicine and Science, 2020)
The interpretation of colonic biopsies can be challenging if the histologic presentation is not characteristic. The association between microscopic colitis and inflammatory bowel disease is weak and unclear. Collagenous colitis has been most frequently reported in association with ulcerative colitis either before or many years after ulcerative colitis is established. There are few reports of Lymphocytic colitis in association with Crohn’s disease. To the best of our knowledge however Crohn’s disease presenting as lymphocytic pattern colitis with granulomas has rarely if ever been reported. We present a case of a 34 year old male who presented initially with perianal abscess and fistula-in-ano and subsequent colonoscopic biopsies demonstrated minimal active chronic colitis with granulomas that progressed to lymphocytic colitis pattern inflammation with granulomas within a period of 6-8 months of suboptimal compliance with therapy. [N A J Med Sci. 2020;1(1):009-013. DOI: 10.7156/najms.2020.1301009] Key Words: Microscopic colitis, Collagenous Colitis, Lymphocytic Colitis, Ulcerative Colitis, Crohn’s disease